A geometric analysis of mastectomy incisions: Optimizing intraoperative breast volume - Chopp, David (Pulsus Group Inc, 2011)
INTRODUCTION: The advent of acellular dermis-based tissue expander breast reconstruction has placed an increased emphasis on optimizing intraoperative volume. Because skin preservation is a critical determinant of intraoperative volume expansion, a mathematical model was developed to capture the influence of incision dimension on subsequent tissue expander volumes. METHODS: A mathematical equation was developed to calculate breast volume via integration of a geometrically modelled breast cross-section. The equation calculates volume changes associated with excised skin during the mastectomy incision by reducing the arc length of the cross-section. The degree of volume loss is subsequently calculated based on excision dimensions ranging from 35 mm to 60 mm. RESULTS: A quadratic relationship between breast volume and the vertical dimension of the mastectomy incision exists, such that incrementally larger incisions lead to a disproportionally greater amount of volume loss. The vertical dimension of the mastectomy incision – more so than the horizontal dimension – is of critical importance to maintain breast volume. Moreover, the predicted volume loss is more profound in smaller breasts and primarily occurs in areas that affect breast projection on ptosis. CONCLUSIONS: The present study is the first to model the relationship between the vertical dimensions of the mastectomy incision and subsequent volume loss. These geometric principles will aid in optimizing intra-operative volume expansion during expander-based breast reconstruction.